Perceptions of Antibiotic Use and Resistance: Are Antibiotics the Dentists' Anxiolytics? - Julie Dormoy; Marc-Olivier Vuillemin; Silvia Rossi; Jean-Marc Boivin; Julie Guillet (MDPI AG, 2021)
Background: Antibiotic resistance is a global health crisis. The aim of this study was to explore dentists' perceptions of antibiotic resistance. Methods: A qualitative method was used. Seventeen dentists practising in the Nancy (Lorraine, France) region were surveyed. They were general practitioners or specialised in oral surgery, implantology, or periodontology. The practitioners took part in semi-structured interviews between September 2019 and July 2020. All of the interviews were transcribed in full and analysed thematically. Results: Four major themes have been selected: attitudes of the dentists in regard to the guidelines, clinical factors that influence prescriptions, non-clinical factors that influence prescriptions, and the perception of antibiotic resistance. The dentists stated that they were very concerned regarding the public health issue of antibiotic resistance. However, they often prescribe according to their own interests and habits rather than according to the relevant guidelines. Conclusions: Although dentists are generally well aware of antibiotic resistance, they often do not adequately appreciate the link between their prescribing habits and the phenomenon of antibiotic resistance. Regular updating of practitioners' knowledge in this regard is necessary, but patients and the general public should also be made more aware of the issue.